Peran Orang Tua Dalam Membangun Financial Education Pada Anak Usia Dini - Irbah, Ariq Nurjannah; Munastiwi, Erni; Riyadi, Ahmad Syafi’i Mufadzilah; Binsa, Ucik Hidayah (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2022)
Financial education needs to be done by parents because parents are an important role in family education. This study aims to determine how the role of parents in conducting financial education in early childhood. The method in this study uses a qualitative approach with four respondents who are domiciled in Magetan, East Java. The results showed that the role of parents in conducting financial education includes 1) parents are able to teach and set an example for children to save from an early age through the introduction of banks, 2) parents are able to provide creative education about finance through saving in a piggy bank that is made as creative as possible or provide an attractive piggy bank according to the child's character, 3) provide motivation for children to save money. The solution is to divert the child's attention, the father's role as a mediator, and communicate what is being taught.